2009
DOI: 10.1103/physrevb.80.184420
|View full text |Cite
|
Sign up to set email alerts
|

Spin-density wave in Cr: Nesting versus low-lying thermal excitations

Abstract: It is well known that present versions of density functional theory do not predict the experimentally observed spin-density wave state to be the ground state of Cr. Recently, a so-called "nodon model" has been proposed as an alternative way to reconcile theory and experiment: the ground state of Cr is truly antiferromagnetic, and the spin-density wave appears due to low-lying thermal excitations ͑"nodons"͒. We examine in this paper whether the postulated properties of these nodons are reproduced by ab initio c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…This choice is motivated by the impossibility to introduce both a spin density wave and a structural defect like a stacking fault or a dislocation in a simulation cell with a reasonable number of atoms. Besides, following the nodon model of Vanhoof et al [20], the SDW appears as a perturbation of the AF phase, which may justify the validity of our approximate description of the magnetic order of Cr below the Néel temperature. Finally, Bacon and Cowlam [26] and Williams and Street [27] have shown that the AF phase becomes more stable than the SDW above roughly 200 K in strained samples containing dislocations, with the Néel temperature of the AF phase going up to 450 K. It appears therefore fully legitimate to study dislocation properties in this AF phase.…”
Section: Stability Of Magnetic Phasessupporting
confidence: 69%
See 1 more Smart Citation
“…This choice is motivated by the impossibility to introduce both a spin density wave and a structural defect like a stacking fault or a dislocation in a simulation cell with a reasonable number of atoms. Besides, following the nodon model of Vanhoof et al [20], the SDW appears as a perturbation of the AF phase, which may justify the validity of our approximate description of the magnetic order of Cr below the Néel temperature. Finally, Bacon and Cowlam [26] and Williams and Street [27] have shown that the AF phase becomes more stable than the SDW above roughly 200 K in strained samples containing dislocations, with the Néel temperature of the AF phase going up to 450 K. It appears therefore fully legitimate to study dislocation properties in this AF phase.…”
Section: Stability Of Magnetic Phasessupporting
confidence: 69%
“…1). However, DFT calculations fail to predict the SDW phase as the ground state and invariably find the AF phase as more stable at 0 K whatever the exchange and correlation functional and the DFT approximations [20][21][22][23][24]. Indeed, all Vanhoof et al [20] using LDA+U, Soulairol et al [21] using both LDA, GGA and mixed LDA-GGA functionals, and Cottenier et al [24] using the FLAPW method with GGA functional, found the SDW to have a higher energy than the AF phase.…”
Section: Stability Of Magnetic Phasesmentioning
confidence: 99%
“…As density functional theory approaches are still insufficient to describe the SDW ground state in Cr (ref. 42), this subtle non-monotonic behaviour is difficult to resolve with ab initio calculations. Here, instead, we argue that Q(P) can be explained by macroscopic free-energy considerations similar to those made for Q(T ) at ambient P, once the pressure dependence of the different contributions to the electronic susceptibility are taken into account.…”
Section: Evolution Of a Non-monotonic Q(t = 0 P)mentioning
confidence: 97%
“…In Cr, there exist only itinerant spins but no local moments, so the nesting nature of the SDW is unambiguous. However, to illustrate the difficulty of the problem, even in this limit densityfunctional-theory calculations [4] have not been able to establish the incommensurate SDW ground state [32,33]. In charge systems, there always exist local positively-charged ions and nested itinerant electron pairs inevitably interact with local ions through the electron-phonon coupling [4,31].…”
Section: Discussionmentioning
confidence: 99%